2014
DOI: 10.1891/0047-2220.45.3.22
|View full text |Cite
|
Sign up to set email alerts
|

Colorecta I Cancer and Rehabilitation Counseling

Abstract: In 2011, the American Cancer Society (ACS) estimated that 141,210 people were diagnosed with colorectal cancer, affecting approximately 1.1 million people. One of those individuals was the lead author of this article, who was diagnosed with colon cancer in December, 2011. As such, this article offers a unique perspective on cancer recovery and rehabilitation from a Certified Rehabilitation Counselor who experienced a transverse colostomy and colectomy. Rehabilitation counselors playa critical role in recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Reduced role functioning and productivity is reported for survivors with an ostomy in comparison to those without (Cotrim and Pereira, 2008;Hornbrook et al, 2017); this conflicts with Yau et al (2009), who found no significant differences between the two groups. Ostomates experienced difficulties with physically demanding tasks such as bending and lifting heavy objects, privacy issues and the extended bathroom time required Hewes and Graney, 2014;Hornbrook et al, 2017;McGrath et al, 2017). For those without an ostomy, the disruption and social embarrassment resulting from altered bowel habits provided a barrier to employment Grant et al, 2011;Hornbrook et al, 2017;McGrath et al, 2017;McMullen et al, 2017).…”
Section: Themesmentioning
confidence: 99%
See 3 more Smart Citations
“…Reduced role functioning and productivity is reported for survivors with an ostomy in comparison to those without (Cotrim and Pereira, 2008;Hornbrook et al, 2017); this conflicts with Yau et al (2009), who found no significant differences between the two groups. Ostomates experienced difficulties with physically demanding tasks such as bending and lifting heavy objects, privacy issues and the extended bathroom time required Hewes and Graney, 2014;Hornbrook et al, 2017;McGrath et al, 2017). For those without an ostomy, the disruption and social embarrassment resulting from altered bowel habits provided a barrier to employment Grant et al, 2011;Hornbrook et al, 2017;McGrath et al, 2017;McMullen et al, 2017).…”
Section: Themesmentioning
confidence: 99%
“…Resumption of employment can be eased by emotional and practical support from co-workers and supervisors, and adaptations to the work day such as starting later, the reduction of business travel, and assignment to less physically and mentally demanding tasks (Appleton et al, 2013;Hewes and Graney, 2014;Hornbrook et al, 2017;McGrath et al, 2017). Reported benefits of RTW for bowel cancer survivors included improved functional wellbeing and overall QoL, social support, a structured routine, an increased sense of worth, distraction from illness, financial benefit and a feeling of returning to normality (Appleton et al, 2013;McGrath et al, 2017).…”
Section: Themesmentioning
confidence: 99%
See 2 more Smart Citations